Phenotype Variation, Correlation and Regression Analysis of Quantitative Traits in Adult Pasundan Bulls at Various Ages - Wibowo, Heru Budi; Mudawamah, Mudawamah; Sumartono, Sumartono (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Pasundan cattle are local cattle as strategic germplasm to be developed.  This study aimed to determine the diversity of Pasundan cattle in quantitative traits of chest circumference and body weight at various ages as a basis for information in future breeding development.  The research method was a case study with purposive sampling whose criteria were bulls aged 25 months and above. The material used was 19 Pasundan bulls kept at the UPTD BPPIBT Pasundan Cattle Ciamis, West Java Province. Variable Observed quantitative traits included chest circumference or CC and body weight or BW at various ages. Data analysis using descriptive statistics, chi-square test, correlation and regression analysis.  The research results show that (1) the variation in the age of the sample cattle used with an average value of 30.11 ± 3.63 months, with a VP value of 13.21 months and a median of 29 months, mode 33 months; (2) the Chi-square test, the results of CC and BW research compared to the Pasundan cattle standard were not significantly different (P>0.05) and very significantly different (P<0.01); (3) phenotype variation (VP) in chest circumference (CC) and body weight (BW) was higher compared to the Pasundan bull standard with the following values: 70.14 vs 138.30 cm and 810.64 vs 1,156 kg; (4) the correlation and regression coefficients on the relationship between age, chest circumference, and body weight were quite strong (r>0.5) with a significantly different regression test (P<0.05).